Risk‐stratified adoptive cellular therapy following allogeneic hematopoietic stem cell transplantation for advanced chronic lymphocytic leukaemia. (7th January 2013) - Richardson, Simon E.; Khan, Iftekhar; Rawstron, Andrew; Sudak, Jagoda; Edwards, Noha; Verfuerth, Stephanie; Fielding, Adele K.; Goldstone, Anthony; Kottaridis, Panagiotis; Morris, Emma; Benjamin, Reuben; Peggs, Karl S.; et al.
Summary Following reduced intensity‐conditioned allogeneic stem cell transplantation (RIC allo‐SCT) for chronic lymphocytic leukaemia (CLL), there is an inverse relationship between relapse and extensive chronic graft‐versus‐host disease (GVHD). We evaluated outcomes in 50 consecutive patients with CLL using the approach of alemtuzumab‐based RIC allo‐SCT and pre‐emptive donor lymphocyte infusions (DLI) for mixed chimerism or minimal residual disease (MRD), with the intention of reducing the risk of GVHD. Forty two patients had high‐risk disease, including 30% with 17p deletion (17p−). Of patients who were not in complete remission (CR) entering transplant, 83% subsequently achieved MRD‐negative CR. Both MRD detection and uncorrected mixed chimerism were associated with greater risks of treatment failure. Nine of sixteen patients receiving DLI for persistent or relapsed disease subsequently attained MRD‐negative CR. With a median follow‐up of 4·3 years, 4‐year current progression‐free survival was 65% and overall survival was 75% (60% and 61% in respectively, patients with 17p−). DLI was associated with a 29% cumulative incidence of severe GVHD and mortality of 6·4%. At last follow‐up, 83% of patients in CR were off all immunosuppressive treatment. In conclusion, the directed delivery of allogeneic cellular therapy has the potential to induce durable remissions in high‐risk CLL without incurring excessive GVHD.